Resilience of the Islamic Economic System in Facing Global Crises: A Review of Macroeconomic Stability Principles and the Experiences of Muslim Countries - Yona Fitri; Khaidar Rahmaini Jamila; Yusrizal; M. Ridwan; Anugerah Fathir Alhadid (Journal of Finance and Islamic Banking, 2026)
Purpose: This study examines the resilience of the Islamic economic system in responding to global financial crises by analyzing its core principles, including the prohibition of riba, profit-and-loss sharing, asset-backed financing, and zakat-based redistribution. Method: This research employs a Systematic Literature Review (SLR) guided by the PRISMA 2020 protocol. Boolean search strings were applied to Scopus, Web of Science, and Google Scholar, yielding 140 records, which were refined through identification, screening, eligibility, and inclusion stages into 25 final sources. The study also applies a structured cross-country comparative analysis of Malaysia, Indonesia, Saudi Arabia, Iran, and Türkiye using macroeconomic and financial stability indicators, including capital adequacy, non-performing financing/loans, credit growth, GDP volatility, and Islamic finance market share. Results: The findings indicate that Islamic financial institutions tend to demonstrate relatively stronger resilience during crisis periods due to risk-sharing mechanisms, asset-backed financing, and restrictions on speculative transactions. However, the effectiveness of this resilience depends on institutional governance, regulatory quality, and Shari’ah supervision. Implications: This study provides insights for regulators and Islamic financial institutions in strengthening governance, harmonizing Shari’ah standards, and developing substantive Islamic financial instruments. Originality: The study integrates a PRISMA-based SLR with indicator-based cross-country comparative analysis to examine Islamic economic resilience.